Effect Of Halloysite Nanotubes On The Performance Of Self-Healing Natural Rubber - Tang, Zi Jie (Universiti Sains Malaysia, 2022)
In this study, a self-healing natural rubber (NR) based on metal-thiolate ion network was developed using halloysite nanotubes (HNT) as filler and the corresponding mechanical and physical properties, morphological, elemental, thermal properties of both HNT filler and self-healing NR/HNT nanocomposites were evaluated. The self-healing capability of the samples were proved by optical microscopy by which the fracture surface nearly healed when two broken pieces were brought in contact with each other. The mechanical properties indicated the tensile strength significantly increased with the increasing of healing time and healing temperature. In contrast, for the evaluation of mechanical performance, Scanning Electron Microscopy (SEM) images reveal that better recovery was achieved in nanocomposites compound with lower filler loading as no obvious gap was observed in lower loading. From tensile and tear test, the optimum filler loading was 8 phr. In contrast, for compression set test, sample with 8 phr exhibit lowest compression set, meaning that the sample was able to retain its elastic properties under compressive force. Also, hardness was enhanced from 12.67 to 18.33 Shore A by the addition of 10 phr HNT. The relative density was increased from 1.01 to 1.03 with the increasing of filler loading from 0 to 10 phr. Fourier-transform infrared spectroscopy (FTIR) confirmed the Si-O and Al-OH in HNT as well as C=S and SCC bonding in zinc thiolate, indicates that the reversible ionic bonding of Zn2+. The results proved that NR/HNT nanocomposites was able to self-healed at room temperature and healed more with the applied of pressure. Also, the reversible ionic supramolecular network was formed within the nanocomposites and contributed to self-healing mechanisms.